2015
DOI: 10.1093/geront/gnu181
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Disorders Among an Invisible Minority: Depression and Dementia Among American Indian and Alaska Native Elders

Abstract: According to the 2010 Census, 5.2 million people identified themselves as American Indian or Alaska Native (AIAN) in the United States. This was an increase of 39% from the prior Census, making AIANs one of the nation's fastest growing populations. The health and social programs reaching them, however, have experienced documented devastating shortfalls. Decades of inadequate resources have resulted in significant health and socioeconomic disparities. AIANs are often considered an "invisible minority." In 2012,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 5 publications
0
40
0
Order By: Relevance
“…Indeed, according to Kramer [45], over 30% of AI/AN older adults visiting an urban Indian Health Services (IHS) outpatient medical facility reported significant depressive symptoms. This statistic is substantially higher than most published estimates of the prevalence of depression among older Whites with chronic illnesses (9–31%) ([49], cited in [27]). In another clinic-based examination, the National Institute of Mental Health [54] (2001) indicated that nearly 20% of AI/AN elders who received primary care reported significant psychiatric symptoms, with rates increasing as a function of age.…”
mentioning
confidence: 54%
See 3 more Smart Citations
“…Indeed, according to Kramer [45], over 30% of AI/AN older adults visiting an urban Indian Health Services (IHS) outpatient medical facility reported significant depressive symptoms. This statistic is substantially higher than most published estimates of the prevalence of depression among older Whites with chronic illnesses (9–31%) ([49], cited in [27]). In another clinic-based examination, the National Institute of Mental Health [54] (2001) indicated that nearly 20% of AI/AN elders who received primary care reported significant psychiatric symptoms, with rates increasing as a function of age.…”
mentioning
confidence: 54%
“…In another clinic-based examination, the National Institute of Mental Health [54] (2001) indicated that nearly 20% of AI/AN elders who received primary care reported significant psychiatric symptoms, with rates increasing as a function of age. Strikingly, the number of AI/AN elders with depression is expected to nearly quadruple to 81,702 cased by 2050 (in comparison with 20,950 cases reported in 2010 [27]).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2 Among AI/NAs, we expect to identify 23,850 persons aged >65 years with dementia in 2010, increasing to 100,980 by 2050. 3 However, a PubMed search readily shows that rigorous studies of aging and cognitive disorders in AI populations are rare.…”
Section: Introductionmentioning
confidence: 99%